Peran Masyarakat dan Swasta dalam Pengelolaan Sampah di Kota Kecil Jawa Tengah (Studi Kasus: Kawasan Kupang Kidul, Kota Ambarawa) - Reni Astuty Manurung (Jurnal Wilayah dan Lingkungan, 2013)
Small cities have strategic role in the contect of regional development. The role of those cities is tightly related to the concept of growth pole and the theory of center place by Christaller. Generally, the role of small cities in village development has 3 basic roles, namely as the center of retail, employment and service (Bajracharya: 2000, Mathur: 1982). But, in the case of urban system, the role of city is identified more from the scale of urban service each cities. Small city can grow as regional service core and the rest can be as local service. Management is a serial of process, habbit, policy, rule and institution which affects direction, management, and control in an enterprise or corporation.  Government, as a local high institution, acts as a primer actor in small city management. Nevertheless, the existence of private and community unconsciously has an important role in the success of small city management. Waste problem is one of many sectors that are noticed in effort of city adaptation to achieve a resilient city.  The act number 18 IX chapter 28 verse (1) defines about community role in waste management which is conducted by government or local government. Ambarawa sub district is a market city which lies on a triangle-circle among Semarang, Solo, and Jogjakarta. Ambarawa is facing a problem which is the form and role of community that is less optimal in city management, such as city waste management.  The purpose of this research is to find out how private and community act in city waste management, particularly in the small cities of central java with case study in Kupang Kidul, Ambarawa City. There are 2 objectives which are to identify who the actor in waste management in Ambarawa and to analyze how the actor acts in waste management in Ambarawa City. This research uses mixed method both quantitative and qualitative. Then, it will be used the methodology of study case as a primary research strategy. Data collection will be carried out by field observation, private and community interview, questionnaire, and document from secondary survey. Beside, analysis technique uses descriptive statistic, with quantitative and qualitative descriptive and scoring analysis. Observation result from this research is that waste management in Kupang Kidul has involved community and private. Nevertheless, private role is scarce so that community has difficulty and problem in waste managemen, especially in case of providing funds. Besides that, there is still a small number of private which considers that waste in the site needs to be managed well. Private sector is still involved individually.